Body Fat Mass Assessment: A Comparison between an Ultrasound-Based Device and a Discovery A Model of DXA. (27th February 2013) - Pineau, Jean-Claude; Lalys, Loïc; Pellegrini, Massimo; Battistini, Nino Carlo
Abstract : Objective . To examine measurement of body composition by ultrasound compared with a reference technique:dual energy X-ray absorptiometry (DXA). We evaluated the accuracy of a portable ultrasound-based device in estimating total body fat mass with those assessed by DXA in adult. Methods . Body fat mass has been estimated using a portable ultrasound-based device in comparison with a contemporary reference DXA apparatus: the Hologic Discovery A. Anthropometric data has been assessed in order to maximize the output of the software associated with the ultrasound-based device. A cross-validation between ultrasound technique (US) and DXA was developed in this study. Total body fat mass estimated by ultrasound was compared with this DXA model in a sample of 83 women and 41 men. Results . Ultrasound technique (US) of body fat (BF) was better correlated with DXA in both women (r 2 = 0.97, P < 0.01 ) and men (r 2 = 0.92, P < 0.01 ) with standard errors of estimates (SEE) being 2.1 kg and 2.2 kg, respectively. Conclusion . The use of a portable device based on a US produced a very accurate BF estimate in relation to DXA reference technique. As DXA absorptiometry techniques are not interchangeable, the use of our ultrasound-based device needs to be recalibrated on a more contemporary DXA.